2019
DOI: 10.3390/nu11112827
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nutritional Quality of Breakfast Cereals Sold on the Italian Market: The Food Labelling of Italian Products (FLIP) Study

Abstract: Breakfast cereals are present on the market as different types and, in general, are one of the food categories in which voluntary information, such as nutrition or health claims (NHC) or gluten free (GF) declarations, have the largest distribution. The aims of the present study were to compare (i) the nutritional declaration among different types of breakfast cereals, as well as among products with and without NHC or GF declarations; and (ii) the salt and sugar contents with the “Italian shared objectives for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 31 publications
13
48
0
Order By: Relevance
“…Breakfast cereals have been extensively studied regarding NCs. Our results show that 77% of them bore NCs, which is in agreement with a previous work in Italy (70%) [ 36 ]. Another study in New Zealand, considering both breakfast cereals and cereal bars, rendered lower values (around 60%) [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Breakfast cereals have been extensively studied regarding NCs. Our results show that 77% of them bore NCs, which is in agreement with a previous work in Italy (70%) [ 36 ]. Another study in New Zealand, considering both breakfast cereals and cereal bars, rendered lower values (around 60%) [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…A priori, one may expect that NCs were only used in healthy foods, so not to mislead consumers. Some analyses have shown an overall better nutrient composition for critical nutrients and energy among foods with NCs compared to those without, although with some conflicting results [ 27 , 28 , 33 , 36 , 41 , 42 , 43 , 44 ]. However, the question still remains as to whether foods carrying NCs are healthy.…”
Section: Discussionmentioning
confidence: 99%
“…As described elsewhere [17], the images of all the sides of the packaging were collected for all the included products, in order to retrieve the following regulated (mandatory) information as listed in the Council Regulation (EU) 1169/2011 [18]: company name, brand name, descriptive name, energy (kcal/100 mL), total fat (g/100 mL), saturates (g/100 mL), carbohydrate (g/100 mL), sugars (g/100 mL), protein (g/100 mL), and salt (g/100 mL). Furthermore, when available other information, i.e., the calcium content (mg/100 mL), the presence of a claim (i.e., presence or absence of at least one NC and of at least one HC as defined by the Council Regulation (EC) 1924/2006 [19]), the presence of the claim "no added sugars" and "source of calcium," and the presence of the organic declaration (as defined by the Council Regulation (EC) No.…”
Section: Data Extractionmentioning
confidence: 99%
“…Other studies have reported that consumers expect that products with nutrition and health claims on the packaging have a better overall nutritional value compared with products without such information [17,18]. Taking these reports into account one must also consider that consumers may be biased and confused from labeling information [19], hence providing nutritional and health information to consumers in an effective way, remains a challenge for the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Food labels are the main method for transferring nutrition and health information of foodstuff to consumers [19]. In Europe, information made on food is regulated by specific laws, including (i) the European Regulation (EU) no 1169/2011, which regulates the mandatory information on food including ingredient lists and nutritional declarations [20]; and (ii) the European Regulation (CE) no 1924/2006, concerning the voluntary nutrition and health claims (NHC) [21].…”
Section: Introductionmentioning
confidence: 99%